2016
DOI: 10.1101/063859
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Colonization and diversification of aquatic insects on three Macaronesian archipelagos using 59 nuclear loci derived from a draft genome

Abstract: 29The study of processes driving diversification requires a fully sampled and well resolved 30 phylogeny. Multilocus approaches to the study of recent diversification provide a powerful 31 means to study the evolutionary process, but their application remains restricted because 32 multiple unlinked loci with suitable variation for phylogenetic or coalescent analysis are not 33 available for most non-model taxa. Here we identify novel, putative single-copy nuclear DNA 34 (nDNA) phylogenetic markers to study the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 101 publications
(111 reference statements)
1
10
1
Order By: Relevance
“…The use of the marker set for C. dipterum developed here resulted in a fully resolved phylogenetic tree in contrast to the mitochondrial tree of Rutschmann et al (2014). The phylogeny of the Cloeon-species complex presented here also is in complete agreement with species tree reconstructions based on 59 nDNA markers (Rutschmann et al, 2016).…”
Section: Resultssupporting
confidence: 67%
“…The use of the marker set for C. dipterum developed here resulted in a fully resolved phylogenetic tree in contrast to the mitochondrial tree of Rutschmann et al (2014). The phylogeny of the Cloeon-species complex presented here also is in complete agreement with species tree reconstructions based on 59 nDNA markers (Rutschmann et al, 2016).…”
Section: Resultssupporting
confidence: 67%
“…These specimens fit Sowa's (1975) concept of Cloeon cognatum Stephens 1835, where C. cognatum is generally treated as a junior synonym of C. dipterum. Under this broad concept, genetic analysis of C. dipterum has recently shown that it includes ≥4 species in Europe, 2 of which are now also present in eastern North America (Rutschmann et al 2017). Specimens used in our study were referred to as species IS1 by Rutschmann et al (2017).…”
Section: Study Animalsmentioning
confidence: 99%
“…Mynott, Webb, & Suter, 2011; Vogler & Monaghan, 2006), or based on the congruency between mitochondrial and nuclear DNA (e.g. Rutschmann et al, 2016).…”
Section: Introductionmentioning
confidence: 99%